Evaluating peroxiredoxin sensitivity towards inactivation by peroxide substrates - Nelson, Kimberly J. (2013)
Peroxiredoxins (Prxs) are very effective peroxide reducing enzymes, but also are susceptible to being oxidatively inactivated by their own substrates. The level of sensitivity to such hyperoxidation varies depending both on the enzyme involved and the type of peroxide substrate. For some Prxs, the hyperoxidation has physiological relevance, so it is important to define approaches that can be used to quantify sensitivity. Here we describe three distinct approaches that can be used to obtain quantitative or semiquantitative estimates of Prx sensitivity and define C(hyp1%) as a simple way of quantifying sensitivity so that values can easily be compared.